Tripartite Motif-Containing Protein 59 (TRIM59) Promotes Epithelial Ovarian Cancer Progression via the Focal Adhesion Kinase(FAK)/AKT/Matrix Metalloproteinase (MMP) Pathway - Zhang, Pei (Med Sci Monit, 2019)
BACKGROUND: The tripartite motif-containing protein 59 (TRIM59) is an important member of the TRIM family, which regulates biological processes. However, the relationship between TRIM59 and epithelial ovarian cancer (EOC) is not clear. MATERIAL/METHODS: The TRIM59 expression level was detected in EOC tissues and cell lines. CCK-8 assay, Transwell assay, and wound healing assay were performed to determine the effects of TRIM59 on EOC cell proliferation, invasion, and migration. Silencing of the expression of TRIM59 in EOC cells and expression of FAK/AKT/MMP pathway-related protein were detected by Western blot analysis. RESULTS: Through bioinformatics analysis, TRIM59 was found to be highly expressed in EOC and was correlated with prognosis of patients. TRIM59 was upregulated in EOC tissues and cells. Silencing TRIM59 significantly suppressed EOC cell proliferation, migration, and invasion. In terms of molecular mechanism, silencing TRIM59 inhibited the FAK/AKT/MMP pathway. CONCLUSIONS: TRIM59 is a biomarker for the prognosis of EOC. It is also oncogenic and a potential target for EOC therapy.